Bird’s Eyeview of Teachers’ Efficacy on Blended Learning - Dioquino, Windy S.; Lariego, Ednalene; Ronel V. Sudaria (Researchparks Publishing, 2023)
The study determined school leader’s viewpoint of teachers’ efficacy on implementation of the blended learning modality in the Schools Division of Valencia City, school year 2022-2023. Specifically, it unravel the school leader’s assessment of teacher’s ability to implement blended learning modality; discover the experiences of school leaders in handling teachers who struggled while using the blended learning modality during and after the teaching- learning process; describe how the Teachers’ cope with the problems they are facing during and after the Blended learning modality; and show how school leaders motivates and get stoked to boost teachers’ effectiveness through Blended Learning Modality. A qualitative approach was employed in this study. Survey and semi-structured interviews were utilized in gathering the data. The participants of this study are the four (4) public elementary and secondary school leaders from the Schools Division of Valencia City. The school leader’s assessment of teacher’s ability to implement blended learning modality includes learners change in behavior, classroom observations, created supplemental materials, and flexibility. The experiences of school leaders in handling teachers who struggled while using the blended learning modality during and after the teaching - learning process include creativity, limited knowledge, congested curriculum, and time management. Teachers coping mechanism with the problems they are facing during and after the blended learning modality include dedication, planning, collaboration, flexibility, and trainings and school leaders motivated and get stoked to boost teachers’ effectiveness through blended learning modality include guidance, affirmation, advices, and collaborative climate.